Defending spaceflight – The echoes of Apollo. (November 2016) - Rovetto, Robert J.
Abstract: This paper defends, and emphasizes the importance of, spaceflight, broadly construed to include human and unmanned spaceflight, space science, exploration and development. Within this discourse, I provide counter-replies to remarks by physicist Dr. Steven Weinberg against my previous support of human spaceflight. In this defense of peaceful spaceflight I draw upon a variety of sources. Although a focus is human spaceflight, human and unmanned modes must not be treated as an either-or opposition. Rather, each has a critical role to play in moving humanity forward as a spacefaring species. In the course of this communication, I also stress the perennial role of space agencies as science and technology-drivers, and their function to provide a stable and unified platform for space programs.